The association between fatty liver disease and blood pressure in a population-based prospective longitudinal study - Lau, Katharina; Lorbeer, Roberto; Haring, Robin; Schmidt, Carsten O; Wallaschofski, Henri; Nauck, Matthias; John, Ulrich; Baumeister, Sebastian E; Völzke, Henry (Journal of hypertension, 2010)
The aim of the present study was to investigate the association of fatty liver disease (FLD) with blood pressure (BP) and hypertension in a general population sample with prospective 5-year follow-up examinations. We used data from the Study of Health in Pomerania, conducted in the northeastern part of Germany. The study population comprised 3191 individuals aged 20-79 years. FLD was defined as the presence of a hyperechogenic pattern of the liver and increased serum alanine transferase (ALT) levels. Multivariable analyses revealed that FLD was associated with increased DBP and hypertension at baseline and with increased SBP and hypertension at follow-up. In individuals with FLD, the chance of hypertension at baseline and follow-up was three-fold higher [odds ratio (OR) 2.8; 95% confidence interval (CI) 1.3-6.2 and OR 3.1; 95% CI 1.7-5.8, respectively] compared to individuals without FLD. In the subgroup of individuals not receiving antihypertensive medication, FLD was associated with all BP-related variables at baseline and follow-up. Analyses further suggest that these associations were independent of alcohol consumption and further confounders. FLD defined by liver hyperechogenity and increased ALT levels is associated with progression of BP over time and incident hypertension. In individuals with FLD, BP should be checked regularly and interventions addressing behavioural risk factors for FLD and hypertension should be initiated if necessary. Ultrasound should be implemented as a method to detect FLD in individuals with increased ALT levels in routine medical care.